Sejarah Intelektual Islam di Bidang Tasawuf: Imam Al-Ghazali, Ibnu Arabi, dan Mulla Shadra - Andriani, Hesti; Rahmawati, Rahmawati; Syukur, Syamzan (LP2M Universitas Islam Ahmad Dahlan, 2024)
This paper discusses the intellectual history of Islam in the field of Sufism and its figures. This study uses library research with a qualitative approach. Sufism in the context of science refers to the spiritual dimension in Islamic teachings that focuses on achieving closeness to God through cleansing the soul. Over time, Sufism has experienced developments marked by the emergence of figures in the field of Sufism. Figures in the field of Sufism play an important role in the development of spiritual teachings in Islam, especially in the aspect of getting closer to God. The views of great figures such as Imam Al-Ghazali, Ibn Arabi, and Mulla Sadra in the field of Sufism have their own differences and uniqueness, although they all contributed greatly to the development of Islamic spirituality. Imam Al-Ghazali in his Sufism views on the purification of the heart, ethics, Sufism practices so as to produce harmony between sharia and Sufism. Ibn Arabi on Wahdat al-Wujud, Divine love. Mulla Sadra on the Integration of philosophy and Sufism (Hikmah Muta'aliyah). All three offer unique approaches that enrich the tradition of Sufism, connecting the spiritual dimensions of Islam with intellectual and ethical ones.